Geochemical characteristics of rare earth elements in the surface sediments from the Spratly Islands of China. Issue 2 (30th January 2017) - Li, Jingxi; Sun, Chengjun; Zheng, Li; Yin, Xiaofei; Chen, Junhui; Jiang, Fenghua
Abstract: The geochemistry of rare earth elements (REE) in surface sediment from Cuarteron reef (N1), Johnson reef (N2), Hugh reef (N3), Gaven reef (N4), Fiery cross reef (N5), and Subi reef (N6) were firstly studied. The total REE abundance (∑ REE) varied from 2.244 μg·g − 1 to 21.661 μg·g − 1, with an average of 4.667 μg·g − 1 . The LREE/HREE was from 2.747 to 9.869, with an average of 3.687, which indicated that the light REE was evidently enriched. Fractionation was observed between LREE and HREE. Gd with a negative anomaly was also detected in all of the stations. The negative anomalies of δEu from 0.11 to 0.25, with an average of 0.22, and the positive anomalies of δCe from 1.38 to 3.86, with an average of 1.63. The REE individual correlation values with Ca, Mn, Mg, Sr were r Ca = − 0.05, r Mn = 0.26, r Mg = − 0.14, and r Sr = 0.08. Highlights: The concentrations of REE in sediment could be accurately measured by MD-ICP-MS. REE contents in the surface sediments of the Spratly Islands were relatively low. The Spratly Islands sediments enriched the LREE, and HREE showed a slight loss. The REE mineralization in sediments was hardly effected by calcified deposition.